A madeira na escultura - Gonçalves, Franciso José (2014)
This dissertation addresses wood as a sculpting material and aims to establish the relationship between its characteristics, work methods and pieces in which its been used. Accordingly, it recalls the biological origins and botanical groups belonging to the trees, its properties, qualities or limitations and the care to have when used in sculpture. Describes the material diversity and relates it with the direct carving and constructive methodologies, referring to its particularities and main phases. Lastly, alludes to a certain abidance of the wood sculpture through time, describing and contextualizing some of the works made with this material